What are injury risk factors for elite wushu athletes? - Jung, T.; Park, K. (Trends in Sport Sciences, 2024)
Introduction: Sports activity not only improves bone mineral density (BMD), bone mass (BM), and cardiopulmonary function, but also increases an incidence of sports injuries. As a result, BMD and BM can affect sports injuries, which in turn can have an impact on overall health and well-being.